EVALUATION AND MEASUREMENT OF DIGITAL LITERACY LEVELS TOWARDS INDEPENDENT DIGITAL MEDIA LITERACY - I Gede Suputra Widharma; Anak Agung Made Dewi Anggreni; Ketut Sumadi; I Nengah Jati , (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
This research aims to evaluate and measure the level of digital literacy among college atmosphere. This research took data from student in LPK Ganesha Indonesia during medium of 2024. It based on nine elements of digital literacy concept. Digital literacy is important skill to use information technology in college and administration process. This research analyze the implementation of digital literacy in academic atmosphere by using mixed methods with approach to an embedded concurrent such as combine quantitative and qualitative method. Quantitative data obtained from survey to measure the level and qualitative data obtained from interview and observation about implementation digital literacy. Analyze results show that most of student was in the medium to advance level with element of re-purposing content has the less value. This results indicated that student should be increase their skills to customization and effective using digital content. There are efforts to increase digital literacy in LPK, but still much room for further development. To recommended that digital literacy must be improve as teaching mechanism that integrated to curriculum. To improve and increase skills of digital literacy is very important to prepare student to get more benefits at the digital era in the future.